Effect of film thickness on the surface, structural and electrical properties of InAlN films prepared by reactive co-sputtering. (1st March 2016) - Afzal, Naveed; Devarajan, Mutharasu; Ibrahim, Kamarulazizi
Abstract: InAlN films of different thicknesses (150 nm, 250 nm, 380 nm, 750 nm and 1050 nm) were grown on Si (111) by means of reactive co-sputtering at 300 °C. Surface morphology results indicated an increase in the grains size and their spacing with increase of the film thickness. The surface of InAlN remained smooth with a slight variation in its RMS roughness from 1.29 nm to 6.62 nm by varying the film thickness. X-ray diffraction patterns exhibited InAlN diffraction peaks with preferred orientation along (002) plane in the thickness range 250 nm to 750 nm, however, the preferred orientation of the film was changed towards (101) plane at 1050 nm. An improvement in the crystallinity of InAlN was observed with increase of the film thickness. Electrical characterization revealed a decrease in the film's resistivity by increasing its thickness to 750 nm, however, the resistivity was found to increase at 1050 nm. The electron concentration indicated an increasing trend whereas changes in the electron mobility were found to be inconsistent with increase of the film thickness.